Cardiovascular magnetic resonance 4D flow derived aortic and pulmonary wall shear stress in pediatric patients with repaired tetralogy of Fallot - Nyström, A.; Dangardt, F.; Synnergren, M.; Wåhlander, H.; Sunnegårdh, J.; Svensson, P.-A.; Lagerstrand, K.; De Lange, C. (Frontiers in Pediatrics, 2025)
BackgroundPatients with repaired tetralogy of Fallot (rTOF) risk dilatation of the pulmonary artery (PA) and the ascending aorta (Ao). Ao and PA wall shear stress (WSS) assessed by cardiovascular magnetic resonance (CMR) 4D flow has been studied in adults while the relationships in children are less explored. The purpose of our study was to evaluate the association between WSS in Ao/PA and vascular remodelling in children with rTOF.MethodsRetrospective evaluation was performed in children with rTOF, with CMR including 4D flow, from January 2019 through 2022. Standardised measurements of WSS were performed in the PA and Ao in patients, and in pediatric controls. WSS values were compared and correlated to valvular patency, volumetrics, function, and demographics.ResultsIn the rTOF group (n = 43), median age of 14 years (range 0–18), most patients had a moderate to severe PA regurgitation (>10%, n = 40 and >25%, n = 31). Indexed mean Ao and PA diameters in the rTOF group were increased vs. controls (p < 0.001 and p = 0.009). Compared to controls (n = 15), the mean/peak PA WSS were significantly increased in rTOF (p < 0.001) but not significantly correlated to Ao/PA dilatation, PA regurgitation or to right ventricular function (R = −0.02–0.24, p = 0.5–0.9).ConclusionPediatric patients with rTOF revealed increased Ao/PA diameters and increased PA WSS compared to controls. There was a positive trend, but no association of WSS to Ao/PA dilatation nor PA regurgitation. Vascular remodelling is undoubtedly multifactorial in patients with rTOF. However, increased WSS could be a contributing factor to late complications in rTOF.